DEMOKRASI DALAM PANDANGAN YUSUF AL- QARADHAWI - M. Alwin Abdillah (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2019)
The theme of democracy is one of the themes that is still interesting to discuss. Various works that deal with democracy have been produced - both by Islamic thinkers and Westerners. Since the arrival of the West to the Islamic world, and along with the progress of the West today, then something that comes from the West has always been an indicator of progress. For this claim so that many countries feel it is important to "follow" - whether directly or indirectly - all forms of progress that have been achieved by the West - including the theme of democracy.